Shadow Prices in Multiple Objective Linear Programming - Kornbluth, J. S. H. (The Journal of the Operational Research Society, 1985)
In two recent papers, the problems of the two-sided nature of shadow prices in degenerate L.P.s have been reviewed. Aukamp and Steinberg demonstrate that shadow prices and the optimal dual variables computed by L.P. packages do not necessarily correspond. Their analysis is completed by Mustafa Akgul, who shows that positive and negative prices can be easily computed by simple auxiliary programmes as well as by parametric programming methods. The original work on this subject by Strum discusses the pricing and accounting aspects of two-sided shadow prices. The purpose of this note is to extend the analysis of Akgul to multiple-objective linear programming (MOLP) models.